Pengaruh Persepsi Kualitas Layanan dan Promosi terhadap Kepuasan Pelanggan Aplikasi PLN Mobile - Iman Maulana; Dedi Supiyadi (Jurnal Bisnis, Manajemen, dan Ekonomi, 2026)
The transformation of digital-based public services requires service providers to not only provide applications but also ensure the quality of the service experience perceived by users. In this context, this study aims to examine the role of perceived service quality and promotion in shaping customer satisfaction with the PLN Mobile application as a form of digital public service in the energy sector. This study uses a quantitative approach with an explanatory design. Data were obtained through a survey of 100 PLN Mobile application users selected based on certain criteria, namely having used the application and utilizing the available service features. The research instrument was compiled in the form of a structured questionnaire with a five-point Likert scale. Data analysis was conducted using multiple linear regression after the data were declared to meet the criteria for validity, reliability, and classical assumptions required in regression analysis. The results show that perceived service quality has a positive and significant influence on customer satisfaction. This finding indicates that the quality of the application user experience, such as system stability, ease of access, and service responsiveness, is a major factor in shaping user satisfaction evaluations. In addition, promotion also has a positive and significant influence on customer satisfaction, although its contribution is relatively smaller compared to perceived service quality. Simultaneous testing shows that both variables together play a role in explaining variations in customer satisfaction with the PLN Mobile application. These findings confirm that the development of digital public services needs to place service quality as a top priority, with promotion as a supporting instrument that strengthens user understanding and expectations of the services provided.